2004
DOI: 10.1016/s1388-2457(03)00345-6
|View full text |Cite
|
Sign up to set email alerts
|

Individual analysis of EEG frequency and band power in mild Alzheimer's disease

Abstract: Objective: This EEG study investigates the role of the cholinergic system, cortico-cortical connections, and sub-cortical white matter on the relationship between individual EEG frequencies and their relative power bands.Methods: EEGs were recorded at rest in 30 normal elderly subjects (Nold), 60 mild Alzheimer disease (AD) and 20 vascular dementia (VaD) patients, comparable for Mini Mental State Evaluation scores . Individual EEG frequencies were indexed by the theta/alpha transition frequency (TF) and by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
251
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(307 citation statements)
references
References 68 publications
(91 reference statements)
38
251
3
1
Order By: Relevance
“…Based on TF and IAF, we estimated the frequency band range for each subject, as follows: d from TF-4 to TF-2, h from TF-2 to TF, low a band (a1 and a2) from TF to IAF, and high a band (or a3) from IAF to IAF + 2. The a1 and a2 bands were computed for each subject as follows: a1 from TF to the middle point of the TF-IAF range, and a2 from such middle point to the IAF peak (Moretti et al, 2004). We found that the bandwidth in a1 and a2 bands differed among the groups.…”
Section: Analysis Of Individual Frequency Bandsmentioning
confidence: 97%
See 2 more Smart Citations
“…Based on TF and IAF, we estimated the frequency band range for each subject, as follows: d from TF-4 to TF-2, h from TF-2 to TF, low a band (a1 and a2) from TF to IAF, and high a band (or a3) from IAF to IAF + 2. The a1 and a2 bands were computed for each subject as follows: a1 from TF to the middle point of the TF-IAF range, and a2 from such middle point to the IAF peak (Moretti et al, 2004). We found that the bandwidth in a1 and a2 bands differed among the groups.…”
Section: Analysis Of Individual Frequency Bandsmentioning
confidence: 97%
“…Traditionally, the a power is evaluated in one or two fixed frequency bands ranging from 8 to 13 Hz. Moreover, the analysis of individual EEG frequency bands (Kopruner et al, 1984;Niedermayer, 1993;Klimesch, 1999) could reveal different sub-bands in the range of the a frequency possibly supporting different cognitive functions (Moretti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies comparing absolute and relative EEG power show that absolute power may yield different results from those obtained using relative power [39][40][41]. Because relative power values exhibit lower group variability than absolute power values and are not affected by the electrical volume conductor properties of the head which influences EEG amplitude [39], relative power is more suitable for comparison between different channels.…”
Section: Data Processingmentioning
confidence: 99%
“…Because relative power values exhibit lower group variability than absolute power values and are not affected by the electrical volume conductor properties of the head which influences EEG amplitude [39], relative power is more suitable for comparison between different channels. For these reasons, average power across epochs in each minute was calculated for each band and overall EEG, respectively.…”
Section: Data Processingmentioning
confidence: 99%